Spatial Analysis for Geometric Parameters of Badush dam Reservoir, Mosul, Northern Iraq - Maha Shaher Badowi; Sabbar Abdullah Saleh; Mohammad Rashid Abood (Tikrit Journal of Pure Science, 2023)
The Iraqi government planned to complete the building of partially constructed Badush dam to protect against the collapse of Mosul Dam on Tigris River northwest of Mosul. The study aimed to derive the ge‎ometric parameters that compatible with the levels ranged 226.5-312 m (a.s.l.) such as reservoir volume, reservoir area, reservoir submerged area, perimeter, and average depth of the water column, which values ranges are 68039-12354976139 m3, 130074-407943574 m2, 130078-410538707 m2, 2.32-594.27 km, and 0.52-30.29 m respectively. These parameters were analyzed against the raising of the level, the spatial analysis of the geometric criteria and its relations with the levels of Badush reservoir showed that the relations between the volume of the positive bodies (islands), the undulated areas above water level which indicate the islands, and the planer areas (projections) of the islands with the level, fluctuates between increase and decrease with an increase in the level, as for the volume of reservoir, the submerged undulated area, the exposed planer area of the water pond, and the average water column depth they increased with the level increasing, unlike the thickness of the islands with the level, which fluctuates in increase and decrease with the level, the geometric analysis of the reservoir showed that Badush Dam is able to absorb the flood wave resulting from the collapse of Mosul Dam, at a level much lower than the level suggested in the preliminary studies that were adopted in the designs, because a large part of the water of Mosul Dam reservoir will remain in the same reservoir when the level is balanced after the collapse. between the two reservoirs, and that the results of this analysis represent a database that will be used in subsequent modifications in the designs.